Avocado seed extract encapsulated in zein nanoparticles as a functional ingredient - Thanida Chuacharoen; Chantana Polprasert; Cristina M. Sabliov (Journal of Agriculture and Food Research)
Nano-delivery of natural compounds has gained increasing attention in the food and pharmaceutical ingredients industry. Avocado seed was extracted by a total lipid extraction and the presence of two acetogenin compounds was confirmed by the high-performance liquid chromatography (LC-MS) technique. Then, the avocado seed extract (Avo) was encapsulated into zein nanoparticles by liquid-liquid dispersion and the formation of zein nanoparticles loaded with avocado seed extract (Avo-ZNPs) was confirmed by FTIR analysis. The Avo-ZNPs with various Avo contents showed an average size ranging from 166.9 ± 14.1 to 305.2 ± 16.2 nm with 0.19–0.26 of polydispersity index (PDI), and a surface charge range was −59.5 ± 8.1 to −32.9 ± 0.4 mV, as measured by dynamic light scattering (DLS). The entrapment efficiency (EE) values were up to 82 % and the highest loading capacity (LoC) was 14.8 %. The Avo-ZNPs were found to have significantly higher antioxidant potency compared to the control, as measured by DPPH and FRAP assays. Moreover, the zein nanoparticles were also biocompatible with the acute myeloid leukemia (AML) cell lines, and encapsulated avocado extract induced leukemia cell death. Thus, zein nanoparticles could be a promising delivery system for natural avocado seed extract to be used in the medical and food industries.